2009
DOI: 10.1143/jjap.48.085001
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Photoluminescence of Nanostructured ZnO Crystal Synthesized by Pulsed-Laser Ablation

Abstract: The optical properties of ZnO nanorods and nanowires grown by our newly developed nanoparticle-assisted pulsed-laser deposition (NAPLD) technique were studied by photoluminescence (PL) spectroscopy. This NAPLD technique, which does not require a catalyst for crystal growth, is expected to synthesize high-quality nanostructured ZnO crystals. The green luminescence (GL) band and ultraviolet luminescence (UVL) observed at low temperature were investigated for these crystals. The UVL band consists of several sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…The energy separation between these phonon replicas, as labeled in Fig. 40(b), matched well with the reported phonon energies in ZnO crystals [1,[360][361][362].…”
Section: Photoluminescencesupporting
confidence: 84%
“…The energy separation between these phonon replicas, as labeled in Fig. 40(b), matched well with the reported phonon energies in ZnO crystals [1,[360][361][362].…”
Section: Photoluminescencesupporting
confidence: 84%
“…This emission was attributed to a free exciton (E x ) transition from the localized level below the conduction band to the valence band. Thus, the E x emission of ZnO measured at 10 K by Sakai et al [13] was 3.376 eV. In fact, this near band energy of BeZnO is very large in comparison with that on ZnO [13].…”
Section: Methodsmentioning
confidence: 87%
“…Thus, the E x emission of ZnO measured at 10 K by Sakai et al [13] was 3.376 eV. In fact, this near band energy of BeZnO is very large in comparison with that on ZnO [13]. Therefore, this means that the ternary BeZnO compound is a material having wide band-gap energy.…”
Section: Methodsmentioning
confidence: 93%
“…We have successfully grown nondoped ZnO nanowires by a newly developed nanoparticle-assisted pulsedlaser deposition (NAPLD) technique that does not require the use of any catalyst [6][7][8][9]. And we also found and demonstrated that these crystals had good crystallinity from low-temperature photoluminescence (PL) measurements [10,11].…”
Section: Introductionmentioning
confidence: 95%